Teori Produksi Dalam Perspektif Islam - Fauziah Nur Hutauruk (STIKes Ibnu Sina Ajibarang, 2023)
The theory of production describes the relationship between the factors of production and the level of production produced. Production is the result of all economic activities carried out by the company. To run production smoothly, the company needs the fulfillment of appropriate inputs. Without these inputs, the production process cannot run efficiently. Companies try to maximize production by using available inputs. By maximizing this production, the profits also increase. The purpose of this paper is to understand the production system from an Islamic point of view. Production is also the main activity in the company's activities. If there are no production activities, the company cannot function to produce products.